1981
DOI: 10.3758/bf03206134
|View full text |Cite
|
Sign up to set email alerts
|

Matching the rate of concurrent tone bursts and light flashes as a function of flash surround luminance

Abstract: Subjects adjusted the rate of a repeating toneburst to match that of a concurrently flashing light, or vice versa. Flashes were viewed in luminous or wholly dark surrounds. Matches usually departed from veridical rate matches, and always were affected in the same direction by changes in surround luminance. Matches were a function of whether subjects controlled the visual or auditory stimulus; also, subjects usually reported "driving" of flash rates by auditory rates when they controlled tone rate, but not when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…A phenomenon that is closely related to the issue of perceived simultaneity is 'auditory driving', or the so-called 'temporal ventriloquist effect' (Gebhard & Mowbray 1959;Shipley 1964;Myers et al 1981;Fendrich & Corballis 2001;Morein-Zamir et al 2003), in which the apparent timing of visual stimuli is influenced or 'captured' by auditory stimuli. For example, multiple tone bursts can cause one light flash to appear to be multiple flashes (Shams et al 2000(Shams et al , 2002Berger et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A phenomenon that is closely related to the issue of perceived simultaneity is 'auditory driving', or the so-called 'temporal ventriloquist effect' (Gebhard & Mowbray 1959;Shipley 1964;Myers et al 1981;Fendrich & Corballis 2001;Morein-Zamir et al 2003), in which the apparent timing of visual stimuli is influenced or 'captured' by auditory stimuli. For example, multiple tone bursts can cause one light flash to appear to be multiple flashes (Shams et al 2000(Shams et al , 2002Berger et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A number of previous studies provide support for this expectation. Gebhard and Mowbray (1959), Myers, Cotton, andHilp (1981), andShipley (1964) demonstrated that when the rate of a repetitive auditory stimulus (presented via earphones) is gradually increased or decreased, the perceived temporal rate of a flickering visual stimulus that is maintained at a physically constant level appears to change in the same manner. This phenomenon has been referred to as "auditory driving" (Gebhard & Mowbray, 1959).…”
Section: Methodsmentioning
confidence: 99%
“…This is the fact that the procedure used for measuring auditory driving has always required the observer to attempt to match one of the two sensory modalities by means of the other. For example, in the study by Myers et al (1981) subjects were instructed to set the rate of a fluttering sound so that it seemed to match a flickering light and vice versa. Clearly, it is not possible in this way to obtain a "pure" measure of the perception of temporal rate in either of the modalities, since the one used to indicate the observer's perception is itself affecting (and being affected by) the one being measured.…”
Section: Methodsmentioning
confidence: 99%
“…This question was of interest because several previous studies had suggested that perception of temporal rate was different for the auditory and visual modalities (Gebhard & Mowbray, 1959;Myers, Cotton, & Hilp, 1981;Welch, DuttonHurt, & Warren, 1986). For example, Welch et al (1986) have shown that subjects' magnitude estimates of temporal rate for a light flashing at a specified frequency are consistently greater than estimates of a tone pulsing at the same frequency.…”
Section: Methodsmentioning
confidence: 99%